The Implementation of Reward and Punishment in Motivating Female Students’ Learning at Ma Mu’allimat NW Anjani, East Lombok - Sofiana; Safinah; Komarudin (Formad English Foundation NTB Jakarta, 2025)
This study investigates the implementation of reward and punishment strategies to enhance female students’ learning motivation at MA Mu’allimat NW Anjani, East Lombok. The research addresses challenges such as low motivation, tardiness, incomplete assignments, and rule violations, focusing on how structured rewards and educative punishments foster discipline, engagement, and active learning. A qualitative case study design was employed, with data collected through classroom observations, structured interviews with the vice principal, teachers, and students, and documentation of school programs and student achievements. Data analysis followed an interactive model of reduction, display, and verification. Findings indicate that rewards, including certificates of appreciation, symbolic gifts, and public announcements of students’ names, effectively increase students’ pride, self-confidence, and intrinsic motivation. Educative punishments, such as additional assignments or material repetition, promote responsibility and awareness of behavioral expectations. The study also identifies key supporting factors, such as collaboration among subject and homeroom teachers, a supportive school environment, and parental involvement, as well as inhibiting factors, including inconsistent teacher application, limited time and budget, and diverse student perceptions. When applied consistently, fairly, and thoughtfully, the combination of reward and punishment creates a balanced, competitive, and positive classroom environment, motivating students to actively engage in learning while fostering discipline and character development. These findings provide practical guidance for educators and reinforce behaviorist and Islamic educational principles in promoting effective student motivation.